2007
DOI: 10.1086/510757
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Active Human Herpesvirus–6 Infection in the Brain: Correlation with Polymerase Chain Reaction Detection in Cerebrospinal Fluid

Abstract: One-half of bone-marrow transplant (BMT) and stem-cell transplant recipients have reactivation of latent human herpesvirus (HHV)-6 2-4 weeks after transplant. Although the detection of viral DNA, RNA, and antigen in brain material confirmed active HHV-6 variant B infection, peak viral loads in cerebrospinal fluid (CSF) and serum occurred 2-4 weeks before death and decreased to low levels before or at autopsy. All autopsy samples consistently demonstrated HHV-6 active infection in the hippocampus. Astrocytic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 16 publications
4
80
0
4
Order By: Relevance
“…Although HHV-6 DNA has been shown to persist longer in CSF compared with plasma or serum, 35 it has also been shown that, when both CSF and plasma have reverted to undetectable levels of HHV-6, active infection may still be ongoing in brain tissue. 43 More complete virologic assessment of patients with HHV-6 and delirium would improve understanding of the viral dynamics of HHV-6-related CNS disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although HHV-6 DNA has been shown to persist longer in CSF compared with plasma or serum, 35 it has also been shown that, when both CSF and plasma have reverted to undetectable levels of HHV-6, active infection may still be ongoing in brain tissue. 43 More complete virologic assessment of patients with HHV-6 and delirium would improve understanding of the viral dynamics of HHV-6-related CNS disease.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid PCR contamination, sample extraction, PCR mastermix preparation, and sample loading were performed at three separate locations in the laboratory. HHV-6 viral load was measured using HHV-6A or 6B-specific U90 primers in TaqMan quantitative PCR with 9700HT Fast Real Time PCR System (Applied Biosystems), as previously described (25,33,34). Briefly, for cell-free specimens, 5 μL of extracted DNA was amplified with a final concentration of 0.5 μM HHV-6A or 6B-specific primers and probes in a 20-μL reaction using TaqMan Universal Mastermix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Autopsy studies of patients who died with HHV-6 encephalitis have shown the hippocampus has strong reactivity against HHV-6, 9,70 and HHV-6 has displayed tropism for astrocytes in the hippocampus. 70 HHV-6B will directly cause neuronal damage based on the finding that HHV-6B localizes to pathologically damaged regions.…”
Section: Pathogenesis: We Do Not Know How Hhv-6 Contributes To Cns DImentioning
confidence: 99%